Performance of clay soil reinforced with fly ash and lignin fiber subjected to freeze-thaw cycles - Orakoğlu, Müge Elif; Liu, Jiankun; Lin, Robin; Tian, Yahu (My University, 2017)
This paper aims to present the results of an experimental investigation related to the unconsolidated undrained triaxial compression behavior of finegrained soil as a function of freeze-thaw cycles, and fly ash–lignin fiber volume fractions. All the measurements were carried out for three selected fly ash fractions (0, 4, and 8%), and five selected lignin fiber fractions (0, 0.25, 0.5, 0.75, and 1%). The specimens were exposed to from 0 to 15 freeze-thaw cycles before testing. It has been observed that for the studied soil, the compression strength of unreinforced soil decreased with an increment the number of freeze-thaw cycles. Moreover, the fly ash–lignin fiber–reinforced soil specimens showed greater effect on compression strength after the 15th freeze-thaw cycle. The greatest amount of strength reduction was obtained on the maximum blend ratios of the lignin fiber. Also, the reduction trend of cohesion was declined for the reinforced soil and the resilient modulus of all soil specimens reduced after the 15th freeze-thaw cycle.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Freeze-thaw cycles; Fly ash; Lignin fiber–reinforced soil; Triaxial strength; Resilient modulus; Cohesive force; Friction angle